2015
DOI: 10.1038/srep13442
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of progesterone for moderate to severe traumatic brain injury: a meta-analysis of randomized clinical trials

Abstract: Progesterone has been shown to have neuroprotective effects in multiple animal models of brain injury, whereas the efficacy and safety in patients with traumatic brain injury (TBI) remains contentious. Here, a total of seven randomized controlled trials (RCTs) with 2492 participants were included to perform this meta-analysis. Compared with placebo, there was no significant decrease to be found in the rate of death or vegetative state for patients with acute TBI (RR = 0.88, 95%CI = 0.70, 1.09, p = 0.24). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The potential therapeutic effects of estrogen and progesterone are beyond the scope of this Review, but they have been well studied in humans and animals. It is worth noting that, although many preclinical studies have indicated a multitude of positive benefits for progesterone treatment post‐TBI, from decreased inflammation and cerebral edema to increased functional skills in rats, a recent meta‐analysis of seven randomized clinical control trials (six of which included a representative female population) failed to demonstrate a significant mortality difference between the progesterone‐treated group and the placebo group and concluded that progesterone did not improve outcomes over placebo after TBI (Hirschberg, ; Lin et al, ). One reason for this discrepancy between preclinical and clinical outcomes probably lies in the heterogeneous nature of human TBI, which is more complex and variable than in laboratory models (Wright et al, ).…”
Section: Sex Differences In Preclinical Outcomesmentioning
confidence: 99%
“…The potential therapeutic effects of estrogen and progesterone are beyond the scope of this Review, but they have been well studied in humans and animals. It is worth noting that, although many preclinical studies have indicated a multitude of positive benefits for progesterone treatment post‐TBI, from decreased inflammation and cerebral edema to increased functional skills in rats, a recent meta‐analysis of seven randomized clinical control trials (six of which included a representative female population) failed to demonstrate a significant mortality difference between the progesterone‐treated group and the placebo group and concluded that progesterone did not improve outcomes over placebo after TBI (Hirschberg, ; Lin et al, ). One reason for this discrepancy between preclinical and clinical outcomes probably lies in the heterogeneous nature of human TBI, which is more complex and variable than in laboratory models (Wright et al, ).…”
Section: Sex Differences In Preclinical Outcomesmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a leading cause of human death and morbidity worldwide and affects as many as 2 million individuals in the United States with 70,000–90,000 new cases annually (Lenzlinger et al, ; Maas et al, ). In recent years, clinical outcome improvement has improved, yet large numbers of patients are unable to make a full recovery (Lin et al, ). Damage to the brain can be separated into two phases, the initial primary physical trauma that results from the physical displacements of the brain tissue, and the second injury, which is the brain's response to the trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this abundance of research suggesting that P4 is beneficial following injury and the success of a few small Phase 2 trials, when larger multicenter Phase 3 trials were conducted, no effect of P4 was found over placebo (Lin et al, ; Schumacher et al, ). Furthermore, many have suggested that while there are limitations to preclinical animal studies by current standards, the Phase 3 trials were designed and conducted well and the problem lies in the fundamental bias in the present practice of scientific inquiry (Schumacher et al, ; Schwamm, ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2,400 patients between 15 and 70 years received a progesterone or placebo therapy after an acute TBI. Disappointingly, they showed no significant differences in the favorable outcome or mortality rate (Lin et al, ; Ma et al, ; Wang et al, ). Therefore, the question arises how these differences in the effect or the deficiency of action of progesterone in various types and regions of the nervous system can be explained.…”
Section: Progesterone and Prsmentioning
confidence: 99%